Experimental and numerical study of NOx formation in a domestic H2/air coaxial burner at low Reynolds number. (15th April 2021) - Lopez-Ruiz, G.; Alava, I.; Urresti, I.; Blanco, J.M.; Naud, B.
Abstract: Thermal NO x formation in H 2 /air jet flames from a coaxial burner is studied experimentally and numerically. The aim is to study possible NO x reduction strategies for domestic gas boiler burners. Following a flame splitting method strategy, a single burner is studied at different inlet powers (from 0.2 to 1.0 kW). The effect of three different fuel-air ratios (or equivalence ratio φ) is considered by varying the coaxial air stream, with fuel-air ratios corresponding to values of φ < 1, relevant for domestic boiler applications (here φ = 0.77, φ = 0.83 and φ = 0.91 ). NO x concentrations increase with increasing inlet power between 0.2 and 0.6 kW and numerical results are in good correspondence with available experimental data. The opposite trend is observed above 0.6 kW and no numerical results are obtained, indicating a transition from laminar to turbulent flames. On the other hand, in contrast to the observations made in turbulent non-premixed flames, reducing the equivalence ratio implies higher NO x concentrations in the low Reynolds number flames considered. The numerical results in the laminar regime are used to highlight and quantify three competing main factors concerning NO x production in order to interpret the experimental observations: the volume of the region where NO x is produced, and within this region, the competition between residence time and NO x reaction rate. Based on this analysis, different design strategies for low NO x hydrogen diffusion burners are finally discussed. Highlights: Hydrogen is a potential fuel for domestic burners. NO x reduction can be achieved by flame splitting method. Laminar and turbulent flames show opposite NO x trends with increasing inlet powers. In low Reynolds number flames lower equivalence ratios imply higher NO x concentrations. Competing factors describing local NO x production intensity can be defined.